2023
DOI: 10.15244/pjoes/157072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Statistical and Deep Learning Methods for Forecasting PM<sub>2.5</sub> Concentration in Northern Thailand

Abstract: This study applies statistical methods and deep learning techniques to forecast the daily average PM 2.5 concentration in northern Thailand, where the concentration is usually high and exceeds the safe level. The data used in the analysis are collected from January 2018 to December 2020 from 16 air monitoring stations. The statistical methods used are Holt-Winters exponential smoothing (ETS), autoregressive integrated moving average (ARIMA), and dynamic linear model (DLM). The deep learning techniques consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Many statistical methods have been used to study and forecast PM concentrations using air pollutants data, such as Holt-Winters exponential smoothing, autoregressive integrated moving average (ARIMA), linear regression model. These methods use collections of probability distribution and assumption to make predictions (Wongrin et al, [10]). In contrast, machine learning is another method to focus on prediction by using learning algorithms to find patterns and can apply to deal with data and make a prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Many statistical methods have been used to study and forecast PM concentrations using air pollutants data, such as Holt-Winters exponential smoothing, autoregressive integrated moving average (ARIMA), linear regression model. These methods use collections of probability distribution and assumption to make predictions (Wongrin et al, [10]). In contrast, machine learning is another method to focus on prediction by using learning algorithms to find patterns and can apply to deal with data and make a prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian scholar Ventura et al (2019) [5] proposed using the Holt-Winters model to predict air quality and got better results in the simulation prediction of PM2.5 in the industrial area of Rio de Janeiro. Wongrin et al (2023) [6] used statistical methods and deep learning techniques to predict daily average PM2.5 concentrations in northern Thailand and showed that ARIMA and ETS models performed better than deep learning methods at most stations. Aladağ (2021) [7] combined wavelet transform and ARIMA models to construct a WT-ARIMA model to predict monthly PM10 concentrations in Erzurum, Turkey, and indicated that the hybrid model gave better predictions than the traditional ARIMA model.…”
Section: Introductionmentioning
confidence: 99%